Confocal scanning raman spectroscopy (CSRS) of an operating organic light-emitting diode - Paez-Sierra, B. A. (2010)
Organic molecules with semiconducting properties are becoming nowadays core of the organic-based electronic era. Although organic light emitting diodes (OLEDs) have already matured for commercial applications, they still require longer device lifetimes. Some of the long-standing challenges in OLED technology relay on degradation and failure mechanisms. Several authors observed that degradation and subsequent damage of OLEDs is accompanied by formation of dark non-emissive spots [1-2]. Implementation of the confocal scanning Raman spectroscopy (CSRS) measurements helps to understand the chemistry, physics of OLEDs and moreover to have better confidence on their quality assurance.